Chlorambucil Conjugated Ugi Dendrimers with PAMAM-NH2 Core and Evaluation of Their Anticancer Activity - Nalin Seixas; Bruno B. Ravanello; Ibrahim Morgan; Goran N. Kaluđerović; Ludger A. Wessjohann (MDPI AG, 2019)
Herein, a new Ugi multicomponent reaction strategy is described to enhance activity and solubility of the chemotherapeutic drug chlorambucil through its conjugation to poly(amidoamine) (PAMAM-NH2) dendrimers with the simultaneous introduction of lipidic (i-Pr) and cationic (⁻NH2) or anionic (⁻COOH) groups. Standard viability assays were used to evaluate the anticancer potential of the water-soluble dendrimers against PC-3 prostate and HT-29 colon cancer cell lines, as well as non-cancerous mouse NIH3T3 fibroblasts. It could be demonstrated that the anticancer activity against PC-3 cells was considerably improved when both chlorambucil and ⁻NH2 (cationic) groups were present on the dendrimer surface (1b). Additionally, this dendrimer showed activity only against the prostate cancer cells (PC-3), while it did not affect colon cancer cells and fibroblasts significantly. The cationic chlorambucil-dendrimer 1b blocks PC-3 cells in the G2/M phase and induces caspase independent apoptosis.